Pengujian Bentuk Pasar Modal Efisiensi Lemah Pada Saham-Saham Perusahaan Sektor Telekomunikasi Sebelum Dan Saat Pandemi Covid-19 - Dibyantoro, Dibyantoro (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2021)
This study aims to examine the weak efficiency of the capital market in Indonesia, especially in the shares of companies based in the telecommunications sector. This condition is associated with the Covid-19 pandemic, namely before and during the Covid-19 pandemic. Where during the Covid-19 pandemic the use of telecommunications in various sectors increased and developed rapidly. The data is taken from the shares of telecommunications companies listed on the Indonesia Stock Exchange (IDX) under the category of the telecommunications sector, where there are six companies during the period January 2019-December 2020. The test analysis methods used are run test, correlation test, and autocorrelation test. using the help of IBM SPSS Statistics 25 Software processing using stock trading data of the four companies for 479 days. The results of the study prove that by going through a run test both before and during the Covid-19 pandemic, the four companies showed stock return data that occurred randomly. Through the correlation test both before and during the Covid-19 pandemic, the four companies showed that there was no correlation between stock returns in period t and stock returns in period t-1.